2012
DOI: 10.1101/gr.117366.110
|View full text |Cite
|
Sign up to set email alerts
|

A systematic study of gene expression variation at single-nucleotide resolution reveals widespread regulatory roles for uAUGs

Abstract: Regulatory single-nucleotide polymorphisms (rSNPs) alter gene expression. Common approaches for identifying rSNPs focus on sequence variants in conserved regions; however, it is unknown what fraction of rSNPs is undetectable using this approach. We present a systematic analysis of gene expression variation at the single-nucleotide level in the Saccharomyces cerevisiae GAL1-10 regulatory region. We exhaustively mutated nearly every base and measured the expression of each variant with a sensitive dual reporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 38 publications
3
34
0
Order By: Relevance
“…Many of these elements were shown to control protein levels by altering the efficiency of translation (7-9, 11), whereas some elements affect translation and in addition, transcription (15) or mRNA degradation (23). Despite much progress, significant challenges remain in deciphering the rules by which multiple elements combine to fine-tune protein expression, as well as in quantifying the degree of expression variation that may be jointly explained by known and novel regulatory elements.Traditionally, the impact of 5′-UTR elements on protein abundance is determined experimentally by comparing a perturbed 5′-UTR sequence with an appropriate control (16,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Although valuable insights emerged from such studies, they frequently focused on the influence of sequence manipulations on a single type of regulatory element.…”
mentioning
confidence: 99%
“…Many of these elements were shown to control protein levels by altering the efficiency of translation (7-9, 11), whereas some elements affect translation and in addition, transcription (15) or mRNA degradation (23). Despite much progress, significant challenges remain in deciphering the rules by which multiple elements combine to fine-tune protein expression, as well as in quantifying the degree of expression variation that may be jointly explained by known and novel regulatory elements.Traditionally, the impact of 5′-UTR elements on protein abundance is determined experimentally by comparing a perturbed 5′-UTR sequence with an appropriate control (16,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Although valuable insights emerged from such studies, they frequently focused on the influence of sequence manipulations on a single type of regulatory element.…”
mentioning
confidence: 99%
“…Values for slopes are provided in Supplemental Table S5, and values for the fold response of each promoter are provided as Supplemental Data. only (e.g., Yun et al 2012), and therefore do not distinguish between mutations affecting burst frequency versus those that modulate burst size. In this study, we relied on the theoretical idea of using gene expression noise to distinguish between those two processes in order to examine the sensitivity of burst size and burst frequency to mutations in promoter sequence.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter case, the upstream ATG probably reduces burst size via nonproductive translation, although some YFP is generated from the original ATG due to ''slippage'' in translation initiation or reinitiation (Meijer and Thomas 2002;Sachs and Geballe 2006). The upstream ATG may also lower transcript levels (Yun et al 2012). The two types of mutations, TATA and upstream ATGs, also appeared in deviating variants from other promoters (Table 1).…”
Section: Noise In Mutated Promoters Scales With Mean Abundancementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a systematic study in Saccharomyces cerevisiae showed that uAUGs exert potent and widespread regulation in both transcription and translation levels (97). Mapping of transcript leaders (5=-UTRs that may contain upstream open reading frames) in translation (TL-seq) revealed that uAUGs are rare in yeast, but when present, they are conserved and functional (4).…”
Section: Discussionmentioning
confidence: 99%